2001
DOI: 10.1002/cncr.9027
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic artifacts and pitfalls of thyroid fine-needle aspiration using ThinPrep®

Abstract: presented in poster form at the United States

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
106
1
11

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 12 publications
4
106
1
11
Order By: Relevance
“…Some studies have shown that conventional smears has a lower rate of nondiagnostic specimens and a higher proportion of accurate diagnosis. [7][8][9][10] More recent studies, however, have supported comparable or better results with liquid-based cytology. [11][12][13] Most published articles discuss thyroid FNAC using the ThinPrep system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that conventional smears has a lower rate of nondiagnostic specimens and a higher proportion of accurate diagnosis. [7][8][9][10] More recent studies, however, have supported comparable or better results with liquid-based cytology. [11][12][13] Most published articles discuss thyroid FNAC using the ThinPrep system.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Most published articles discuss thyroid FNAC using the ThinPrep system. [7][8][9][10]12,13 The reported inadequate rates varied from 22% up to 41%. Sensitivity and specificity varied from 87% to 94% and from 67% to 99%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been introduced to obtain thin-layer smears in cervical cytology. The excellent results in this field prompted a wider application to virtually all cytological branches, including thyroid FNAB (20)(21)(22)(23)(24)(25)(26)(27). The current investigation has been carried out to evaluate the effectiveness of a panel made up by HBME-1 and Galectin-3 on LBC in identifying two subsets of FN/AUS with low and high malignant risk that might be managed differently to achieve a reduction of inappropriate surgery.…”
Section: Introductionmentioning
confidence: 99%
“…For example, diagnostic cells are famously smaller in TP. [3][4][5] In thyroid cytology, several alterations have been reported, including reduction and alteration in colloid, decreased pseudo-inclusions in cases of papillary cancer, and difficulty recognizing Hashimoto thyroiditis in TP compared with CPs. 3,6 Despite these alterations, several large studies have proven that TP is at least equivalent to CPs in diagnostic accuracy and is a safe alternative to CPs in thyroid cytology.…”
mentioning
confidence: 99%
“…[3][4][5] In thyroid cytology, several alterations have been reported, including reduction and alteration in colloid, decreased pseudo-inclusions in cases of papillary cancer, and difficulty recognizing Hashimoto thyroiditis in TP compared with CPs. 3,6 Despite these alterations, several large studies have proven that TP is at least equivalent to CPs in diagnostic accuracy and is a safe alternative to CPs in thyroid cytology. 7,8 Settings or specific diagnoses in which background material is critical to establishing the diagnosis (some sarcomas, salivary gland tumors, mucinous tumors) may be more difficult to accurately diagnose with TP.…”
mentioning
confidence: 99%